(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
Comparative analysis of the quantitative composition of proteins, amino acids, vitamins and fatty acids in samples taken from legumes - peanuts, beans, legumes and stalks. Proportions and differences in the organic composition of plant grains and stems were studied. All comments were given according to utilizing from them